Foliar Application of a Microbial Inoculant and Alkali-Extracted Humic Product Boosts Forage Productivity and Quality on a Central Coast California Rangeland - Carey, Chelsea J.; Strohm, Hayley; Smith, Ford; Biaggi, Mark (Frontiers in Sustainable Food Systems, 2022)
There is increasing interest in using biostimulant products, such as microbial inoculants and alkali-extracted “humic” substances to help manage rangelands regeneratively and rebuild soil health. Understanding how plant and soil communities on rangelands respond to these products is therefore important. In this 3-year study, we examined the combined effects of a commercial inoculant and alkali-extracted “humic” product that are currently on the market (Earthfort Inc. Soil Provide and Revive®) and asked whether they influenced rangeland forage productivity and quality, soil microbial biomass and community composition, and abiotic soil parameters in Central Coastal California. Treatments were established in February 2018 and the products were applied two to three times a year during the growing season (approximately November—May). Sampling of plant and soil samples also began in February 2018 and continued in the fall and spring for three consecutive growing seasons. We found that forage productivity responded positively to the foliar application of these commercial products, with forage production on average 58% percent higher in treated compared to control sites. Some metrics of forage quality (acid detergent fiber, calcium, and fat content) also responded in a desirable way, but these benefits were not mirrored by changes belowground in the microbial community or abiotic parameters. While our study derives from one ranch and therefore requires confirmation of its ubiquity prior to broadscale adoption, our results provide new insights into the usefulness of this approach for managing rangeland productivity in California's Central Coast—and suggest biostimulants could warrant attention as a potential tool for regenerative stewardship of rangelands more broadly.